PERSEPSI GURU SMA NEGERI KOTA PEKANBARU TERHADAP UNDANG-UNDANG NOMOR 8 PASAL 10 TAHUN 2016 TENTANG PENYANDANG DISABILITAS - Octaviana, Lia; Erlinda, Sri; Supentri, Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is based on the coming out of the rules about persons with disabilities (PwDs) are allowed to go to public schools, namely Law No. 8 article 10 of 2016. However, from this rule teachers who usually teach ordinary students and now teach students with disabilities. Then, generate a variety of perceptions.FA So the author wants to know how the teacher's perception of the Act. The formulation of the problem in this study is how teachers' perceptions, what are the factors of teacher's difficulties, and whether the teacher's efforts in dealing with PwDs. The population in this study was the total teachers of State Senior High School Pekanbaru which amounted to 885 people and the sample in this study was 89 teachers. The instruments of data collection were observation, questionnaire, interview and documentation. Data analysis with descriptive quantitative and qualitative descriptive. The results showed that teachers' perceptions of Law No. 8 of article 10 of the year 2016 is good 72.8% is in the range 67.00% -100%. Furthermore, teachers' difficulties in dealing with PwDs are that teachers are not skilled in dealing with persons with disabilities (teacher professionalism), contact experience with students with special needs, student condition, and lack of facilities. Furthermore, the teacher's efforts in dealing with PwDs during the teaching-learning process is to plan teaching and learning activities, conduct teaching and learning activities, and foster interpersonal relationships. Keywords: Perception, Disability